A review on noble-metal-free bifunctional heterogeneous catalysts for overall electrochemical water splitting - Yan, Ya (2017)
Production of hydrogen by water splitting is an appealing solution for sustainable energy storage. Development of bifunctional catalysts that are active for both the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) is a key factor in enhancing electrochemical water splitting activity and simplifying the overall system design. Here, recent developments in HER–OER bifunctional catalysts are reviewed. Several main types of bifunctional water splitting catalysts such as cobalt-, nickel- and iron-based materials are discussed in detail. Particular attention is paid to their synthesis, bifunctional catalytic activity and stability, and strategies for activity enhancement. The current challenges faced are also concluded and future perspectives towards bifunctional water splitting electrocatalysts are proposed.